Village Drama Against Malaria. - Lim, R; Peto, T; Tripura, R; Cheah, P (Elsevier, 2016)
The Village Drama Against Malaria project used Cambodian drama, art, music workshops, and village concerts to mobilise rural communities in areas with the highest prevalence of malaria in Battambang province, western Cambodia. By involving local people in performances, the project aimed to provide health education in a fun and engaging way to support the village malaria workers. Cambodian drama uses caricatures in a funny and irreverent way to weave health education into stories. The project combined traditional entertainment with the modern; drones were used to film the village and photos and videos were shared across the province on Facebook. The project engaged villagers and attracted most people in each of the villages, including those who might otherwise not have received health education.